2023
DOI: 10.1186/s40662-023-00363-0
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal diagnostics for keratoconus and ectatic corneal diseases: a paradigm shift

Renato Ambrósio,
Marcella Q. Salomão,
Lorena Barros
et al.

Abstract: Different diagnostic approaches for ectatic corneal diseases (ECD) include screening, diagnosis confirmation, classification of the ECD type, severity staging, prognostic evaluation, and clinical follow-up. The comprehensive assessment must start with a directed clinical history. However, multimodal imaging tools, including Placido-disk topography, Scheimpflug three-dimensional (3D) tomography, corneal biomechanical evaluations, and layered (or segmental) tomography with epithelial thickness by optical coheren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 106 publications
0
2
0
Order By: Relevance
“…Scheimpflug imaging using rotating corneal tomography and ultra-high-speed biomechanical assessments provides valuable data for accurate diagnosis and treatment planning. Several studies have already demonstrated their significance in detecting an increased susceptibility to ectasia [14][15][16]. This case underscores the importance of investigating ocular biomechanics for precise IOP measurement, offering insights into the actual effects of IOP fluctuations on corneal biomechanical measurements.…”
Section: Case Reports In Ophthalmologymentioning
confidence: 66%
“…Scheimpflug imaging using rotating corneal tomography and ultra-high-speed biomechanical assessments provides valuable data for accurate diagnosis and treatment planning. Several studies have already demonstrated their significance in detecting an increased susceptibility to ectasia [14][15][16]. This case underscores the importance of investigating ocular biomechanics for precise IOP measurement, offering insights into the actual effects of IOP fluctuations on corneal biomechanical measurements.…”
Section: Case Reports In Ophthalmologymentioning
confidence: 66%
“…We agree with Navarro-Naranjo et al in their letter that multimodal diagnostics, beyond front surface topography and 3-D tomography, is essential to augment the safety and efficiency of refractive surgery. 4 Corneal biomechanical assessment, integrated with tomography with artificial intelligence, aims to characterize the corneal predisposition or susceptibility to biomechanical decompensation. 4,5 This concept goes beyond, but not over, the detection of mild or subclinical (fruste) cases of keratoconus.…”
Section: Dear Editormentioning
confidence: 99%
“…4 Corneal biomechanical assessment, integrated with tomography with artificial intelligence, aims to characterize the corneal predisposition or susceptibility to biomechanical decompensation. 4,5 This concept goes beyond, but not over, the detection of mild or subclinical (fruste) cases of keratoconus. The BrAIN (Brazilian Artificial Intelligence Networking in Medicine) ectasia software combines with AI the intrinsic predisposition and the extrinsic impact of the corneal procedure to objectively characterize ectasia risk (https://brain.med.br/).…”
Section: Dear Editormentioning
confidence: 99%
“…Identifying early-stage and subclinical ectatic corneal conditions has become increasingly important, as such cases are particularly vulnerable to post-LVC iatrogenic ectasia. The current concept for assessing ectasia risk before refractive surgery is to consider data beyond (not over) the corneal anterior surface with a multimodal approach to characterize ectasia susceptibility [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%